Liquid crystal polyesterimide based on bio-based diamine and preparation method of liquid crystal polyesterimide

The imide diacid monomer prepared by using bio-based diamines and one-step melt polycondensation method combined with trimellitic anhydride is prepared to obtain a liquid crystal polyesterimide polymer, which solves the problem of poor processing performance of liquid crystal polyaryl, achieves better processing performance and thermomechanical properties, and ensures the environmental friendliness of the material.

CN119570031APending Publication Date: 2025-03-07DONGHUA UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411626396.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The processing performance of existing liquid crystal polyaryl esters is poor, resulting in limited preparation and molding.

Method used

A bio-diamine-based imide diacid monomer was prepared by reaction with trimellitic anhydride and bio-diamine, and then a liquid crystal polyesterimide polymer was prepared by a one-step melt polycondensation method.

Benefits of technology

The processing performance of liquid crystal polymers is significantly optimized, melt viscosity is reduced, thermomechanical properties are improved, and the environmental friendliness and sustainability of the materials is improved due to the use of bio-based raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570031A_ABST
    Figure CN119570031A_ABST
Patent Text Reader

Abstract

The invention relates to liquid crystal polyesterimide based on bio-based diamine and a preparation method of the liquid crystal polyesterimide, the processing performance of a high-performance liquid crystal polymer can be effectively optimized by a bio-based imide diacid monomer, and the environment friendliness of the liquid crystal polymer is ensured by a bio-based raw material source; a new strategy is provided for developing a next-generation high-performance polymer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of liquid crystal polymers, and in particular relates to a liquid crystal polyester imide based on bio-based diamine and a preparation method thereof. Background Art

[0002] High-performance liquid crystal polymers are widely used in cutting-edge fields such as aerospace, electronics and electrical engineering due to their excellent mechanical properties, dielectric properties and thermal stability. However, the fully aromatic molecular structure causes the liquid crystal polymer to have a high melting point and a high melt viscosity, which in turn leads to poor processing performance, limiting subsequent processing and molding. Therefore, optimizing the processing performance of high-performance liquid crystal polymers through the molecular structure design of liquid crystal polymers is of great significance for their subsequent processing and molding. Naphthalene-containing monomers are a common monomer for preparing high-performance liquid crystal polymers. Compared with benzene ring monomers, they can increase the number of molecular chain conformations of high-performance liquid crystal polymers by virtue of the "side-step effect" in the molecular chain, thereby improving their processing performance. For example, in patent CN116178689A, naphthalene-containing monomers are copolymerized with a variety of liquid crystal base monomers to obtain a type of liquid crystal polyarylate with low dielectric constant and excellent processing performance. However, at present, naphthalene-containing monomers (such as 2,6-naphthalene dicarboxylic acid, etc.) are mainly prepared based on fossil resources, which poses the challenge of non-renewable resources, and the production process of naphthalene-containing monomers is complex and the production cost is high, which increases the production cost of high-performance liquid crystal polymer resins. In view of this development situation, the development of high-performance liquid crystal polymer resins and their monomers with excellent processing performance based on widely available green and renewable biomass resources is of great significance to the development of high-performance liquid crystal polyarylates. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a liquid crystal polyester imide based on bio-based diamine and a preparation method thereof, so as to solve the problems that the existing traditional liquid crystal polyarylate has poor processing performance and is limited in preparation and molding.

[0004] The present invention provides a polyester imide polymer, the general structural formula of the polyester imide polymer is:

[0005]

[0006] Wherein R is selected from (CH2) m ; a+b+c+d=1, 0.4≤a≤0.6, 0.15≤b≤0.2, 0.2≤c≤0.3, 0.05≤d≤0.1; n≥20.

[0007] The m≥4;

[0008] Preferably, m=4-20.

[0009] Preferably, the polyesterimide polymer comprises:

[0010]

[0011] Among them, a+b+c+d=1, 0.4≤a≤0.6, 0.15≤b≤0.2, 0.2≤c≤0.3, 0.05≤d≤0.1; n≥20.

[0012] The present invention provides a method for preparing a polyester imide polymer, comprising:

[0013] The monomers, acetic anhydride and catalyst are mixed, pre-reacted and cooled under protective gas conditions to obtain a polyester imide polymer; wherein the monomers are imide diacid, p-hydroxybenzoic acid, terephthalic acid and biphenol.

[0014] Preferably, the molar ratio of the imide diacid, p-hydroxybenzoic acid, terephthalic acid and biphenol is 5-10:40-60:15-20:20-30; the molar amount of acetic anhydride is 1.1 to 1.5 times the molar amount of hydroxyl groups in the feed monomers (biphenol and p-hydroxybenzoic acid); and the catalyst feed amount is 0.1 to 0.5% of the total mass of the monomers (imide diacid, p-hydroxybenzoic acid, terephthalic acid and biphenol).

[0015] Preferably, the pre-reaction comprises: pre-reacting at 135-145° C. for 60-90 min under a protective gas atmosphere.

[0016] Preferably, after the pre-reaction is completed, the reaction system is heated to 280-320° C., and a vacuum of 1-5 mbar is provided at the end of the reaction (such as when the product climbs the rod or forms a mass) to remove the by-products in the reaction system, and the negative pressure time is 10-90 min;

[0017] Preferably, the cooling is natural cooling under protective gas conditions; and after the cooling, the mixture is ground or pulverized into fine particles.

[0018] The protective gas is nitrogen or an inert gas.

[0019] Preferably, the catalyst includes one or more of potassium acetate, lead acetate, aluminum chloride and zinc chloride.

[0020] The structure of the imide diacid:

[0021] Where m≥4.

[0022] Further, the imide diacid comprises the following structure:

[0023]

[0024] One of them.

[0025] Preferably, the preparation of the imide diacid includes: obtaining it by reaction with raw materials containing trimellitic anhydride and bio-based diamine; wherein the bio-based diamine monomer is one or more of butanediamine, pentamethylenediamine, and decanediamine; the molar ratio of trimellitic anhydride to the bio-based diamine monomer is 1-2:1; the reaction is condensed and refluxed for 1 to 3 hours, wherein the condensation and reflux temperature is 120 to 160°C.

[0026] Furthermore, the preparation of the imide diacid includes: mixing trimellitic anhydride with a solvent, stirring and heating to 80-160° C., adding bio-based diamine after the trimellitic anhydride is completely dissolved in the solvent, condensing and refluxing for 1-3 hours, purifying, and drying to obtain the imide diacid.

[0027] The amount of the solvent is 1-6 times the total mass of the monomer feed; the solvent is acetic acid; the purification comprises: after the reaction is completed, the reactant solution is cooled to room temperature, the solvent is removed by suction filtration, and the suction filtration product is washed with ethanol solvent.

[0028] The present invention provides an application of the polyester imide polymer in the fields of special engineering plastics, high-performance fibers, etc.

[0029] Beneficial Effects

[0030] (1) The bio-based imide diacid monomers of the present invention can effectively optimize the processing performance of high-performance liquid crystal polymers, and the source of bio-based raw materials ensures the environmental friendliness of liquid crystal polymers, providing a new strategy for the development of next-generation high-performance polymer materials;

[0031] (2) The present invention prepares an imide diacid monomer using trimellitic anhydride and a bio-based diamine in advance, and then uses the monomer to prepare a bio-based liquid crystal polyester imide polymer with both processability and heat resistance by a one-step melt polycondensation method.

[0032] (3) The liquid crystal polyester imide prepared based on bio-based organic amines of the present invention not only has good processing performance, but also can maintain excellent thermomechanical properties at high temperatures, which can meet the application requirements of liquid crystal polymers;

[0033] (4) The imide diacid monomer in the present invention uses bio-based organic amine as raw material, which is green and environmentally friendly, overcoming the shortage of traditional petroleum-based raw materials. It can not only reduce the dependence of high-performance liquid crystal polymer preparation on petrochemical products, but also reduce the pollution to the environment during its production process;

[0034] (5) The method for preparing the imide diacid monomer in the present invention has a simple process, mild reaction conditions, high yield, and simple post-processing of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1The temperature rise melting curves of Example 1, Example 2 and Comparative Example;

[0036] Figure 2 The modulus-temperature curves of Example 1, Example 2 and Comparative Example;

[0037] Figure 3 The rheological curves of Example 1, Example 2 and Comparative Example are shown in FIG. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0039] Table 1 Experimental materials and reagents

[0040] name Specification factory Parabens 99.9% Shanghai MacLean Biochemical Technology Co., Ltd. Pentamethylenediamine 99% Heilongjiang Yipin Biotechnology Co., Ltd. Butanediamine 99% Tianjin University of Science and Technology Decanediamine 99% Shanghai MacLean Biochemical Technology Co., Ltd. Trimellitic anhydride 99.5% Beijing Bailingwei Technology Co., Ltd. Terephthalic acid 99.9% Hengyi Petrochemical Co., Ltd. Bisphenol 99.9% Jiangsu Runfeng Synthetic Technology Co., Ltd. Acetic anhydride 98.5% Shanghai Titan Technology Potassium acetate 99% Beijing Inotech Technology Co., Ltd.

[0041] Example 1

[0042] This embodiment prepares a liquid crystal polyester imide polymer based on an imide diacid monomer, and the method is as follows:

[0043] (1) Add 130 mL of acetic acid and trimellitic anhydride (0.1 mol, 19.21 g) to a three-necked flask. Heat at 120°C until the solution is clear, add diaminobutane (0.05 mol, 4.4 g), and reflux at 140°C for 1 h. Cool the reactants to 25°C, remove the acetic acid by suction, and wash with ethanol until there is no sour smell. Dry in an oven (80°C, 24 h) to obtain imide diacid monomer powder.

[0044] (2) Place p-hydroxybenzoic acid (0.60 mol, 82.8 g), terephthalic acid (0.15 mol, 33.2 g), biphenyl (0.20 mol, 37.2 g), imide diacid (0.05 mol, 21.8 g), and potassium acetate (0.175 g) in a 250 mL three-necked flask and add 95 mL of acetic anhydride. The flask is equipped with a metal paddle stirrer, a nitrogen inlet pipe and control valve, and a heat-insulating distillation head.

[0045] (3) The reaction system was heated to 135°C at a heating rate of 1°C / min in a nitrogen atmosphere and then pre-reacted for 60 minutes. After the pre-reaction was completed, the temperature was raised to 280°C and the viscosity of the product was observed. When the product began to climb the rod or agglomerate, vacuum was started. When the vacuum degree reached 1 mbar, the vacuum was stopped and the heating was turned off after 10 minutes of reaction. The product was naturally cooled to room temperature in a nitrogen atmosphere, removed from the flask, and crushed into fine particles to obtain the final product, the structural formula of which is as follows:

[0046]

[0047] Example 2

[0048] This embodiment prepares a liquid crystal polyester imide polymer based on an imide diacid monomer, and the method is as follows:

[0049] (1) Add 130 mL of acetic acid and trimellitic anhydride (0.1 mol, 19.21 g) to a three-necked flask. Heat at 120°C until the solution is clear, add diaminobutane (0.05 mol, 4.4 g), and reflux at 140°C for 1 h. Cool the reactants to 25°C, remove the acetic acid by suction, and wash with ethanol until there is no sour smell. Dry in an oven (80°C, 24 h) to obtain an imide diacid monomer powder (structure as follows).

[0050] (2) Place p-hydroxybenzoic acid (0.40 mol, 55.2 g), terephthalic acid (0.20 mol, 33.2 g), biphenyl (0.30 mol, 55.8 g), imide diacid (0.10 mol, 43.6 g), and potassium acetate (0.187 g) in a 250 mL three-necked flask and add 95 mL of acetic anhydride. The flask is equipped with a metal paddle stirrer, a nitrogen inlet pipe and control valve, and a heat-insulating distillation head.

[0051] (3) The reaction system was heated to 145°C at a heating rate of 1°C / min in a nitrogen atmosphere and pre-reacted for 60 minutes. After the pre-reaction was completed, the temperature was raised to 320°C and the viscosity of the product was observed. When the product began to climb the rod or agglomerate, vacuum was started. When the vacuum degree reached 5 mbar, the vacuum was stopped and the heating was turned off after 10 minutes of reaction. The product was naturally cooled to room temperature in a nitrogen atmosphere, removed from the flask, and crushed into fine particles to obtain the final product, the structural formula of which is as follows:

[0052]

[0053] Comparative Example 1

[0054] This comparative example prepares liquid crystal polyarylate by the following method:

[0055] (1) Place p-hydroxybenzoic acid (0.60 mol, 82.8 g), terephthalic acid (0.20 mol, 33.2 g), biphenyl (0.20 mol, 37.2 g) and potassium acetate (0.1532 g) in a 250 mL three-necked flask and add 95 mL of acetic anhydride. The flask is equipped with a metal paddle stirrer, a nitrogen inlet pipe and control valve, and a heat-insulating distillation head.

[0056] (3) Heat the reaction system to 140°C at a heating rate of 1°C / min in a nitrogen atmosphere and pre-react for 60 minutes. After the pre-reaction is completed, heat to 300°C and keep constant temperature to observe the change in product viscosity. When the product begins to climb the rod or agglomerate, start evacuating the product. When the vacuum degree reaches 1 mbar, stop evacuating the product and turn off the heating after 10 minutes of reaction. After the product is naturally cooled to room temperature in a nitrogen atmosphere, remove it from the flask and crush it into fine particles to obtain the final product, the structural formula of which is as follows:

[0057]

[0058] The performance of Examples 1 to 2 and Comparative Examples was tested.

[0059] 1) Differential Scanning Calorimetry (DSC)

[0060] The test procedure is as follows: weigh 5-10 mg of the target sample and seal it in an aluminum crucible, place it in a nitrogen atmosphere, heat it from 40°C to 350°C at 20°C / min, keep it constant for 1 min, cool it down to 40°C at 20°C / min, keep it constant for 1 min, heat it up to 350°C at 20°C / min, keep it constant for 1 min, and cool it down to 40°C at 20°C / min.

[0061] 2) Thermogravimetric analysis (TGA)

[0062] The test procedure is as follows: take 5 mg of the target sample and place it in a nitrogen atmosphere, and heat it from 40°C to 600°C at a heating rate of 10°C / min. The temperature corresponding to 95% of the sample weight is taken as the thermal decomposition temperature (T d,5% ).

[0063] 3) Dynamic Mechanical Thermal Analyzer Test (DMA)

[0064] The test procedure is: nitrogen atmosphere, frequency of 1 Hz, temperature rise from room temperature (40°C) to 300°C at 5°C / min. Thin film samples of (10±1) mm×(1±0.2) mm×(0.2±0.05) mm are used.

[0065] 4) Rheological test

[0066] The test procedure is as follows: the test sample is a LCP disc with a diameter of 25 mm and a thickness of 0.5 mm.-1 The temperature was raised to 350°C at a rate of 1 Hz, an amplitude of 0.1%, and a normal force of 1N.

[0067] The DSC test was performed on Example 1, Example 2 and Comparative Example at a heating / cooling rate of 20°C / min in a nitrogen atmosphere (eg Figure 1 ), none of the three samples showed obvious melting peaks, which was due to the poor crystallization ability of the liquid crystal polymer due to the random molecular chains, and thus no melting peak was shown. The liquid crystal transition temperature of the liquid crystal polymer was obtained according to the hot stage polarizing microscope. After the introduction of the imide diacid monomer, the liquid crystal transition temperature of the liquid crystal polymer was reduced to 310-320°C, and the processing performance was significantly optimized.

[0068] The melt rheological behavior of Example 1, Example 2, and Comparative Example was characterized by a high temperature rotational rheometer. The melt viscosity is shown in Table 1. The melt viscosity of the high performance liquid crystal polymer prepared in Example 1 and Example 2 is significantly reduced to 308Pa·s and 133Pa·s, respectively, indicating that the introduction of imidic acid can significantly optimize the processing performance of liquid crystal polymers. According to the characterization results of thermogravimetric analysis, Example 1, Example 2, and Comparative Example all have good thermal stability (396°C <T d,5% <400℃), this high performance liquid crystal polymer has a good processing window.

[0069] The thermal mechanical properties of Example 1, Example 2 and the comparative example were analyzed by a dynamic thermal mechanical analyzer (eg Figure 2 ), Example 1 and Example 2 still maintain storage moduli of 366 MPa and 360 MPa at 200°C, showing high-temperature thermomechanical properties comparable to those of the comparative example (370 MPa).

[0070] Table 1: Physical properties of Example 1, Example 2 and Comparative Example

[0071]

Claims

1. A polyester imide polymer, characterized in that The general structural formula of the polyesterimide polymer is: Wherein R is selected from (CH2) m ; a+b+c+d=1, 0.4≤a≤0.6, 0.15≤b≤0.2, 0.2≤c≤0.3, 0.05≤d≤0.1, n≥20.

2. The polyester imide polymer according to claim 1, characterized in that: The m=4-20.

3. The polyester imide polymer according to claim 1, characterized in that: The polyesterimide polymer comprises: Among them, a+b+c+d=1, 0.4≤a≤0.6, 0.15≤b≤0.2, 0.2≤c≤0.3, 0.05≤d≤0.1; n≥20.

4. A method for preparing a polyester imide polymer, comprising: The monomer, acetic anhydride and catalyst are mixed, pre-reacted and cooled under protective gas conditions to obtain a polyester imide polymer; The monomers include imide diacid, p-hydroxybenzoic acid, terephthalic acid, and biphenol.

5. The preparation method according to claim 4, characterized in that: The molar ratio of the imide diacid, p-hydroxybenzoic acid, terephthalic acid and biphenol is 5-10:40-60:15-20:20-30; the molar amount of acetic anhydride is 1.1-1.5 times the molar amount of hydroxyl groups in the monomers; and the catalyst feed amount is 0.1-0.5% of the total weight of the monomers.

6. The preparation method according to claim 4, characterized in that: The catalyst comprises one of potassium acetate, lead acetate, aluminum chloride and zinc chloride; the imide diacid comprises the following structure: Where m≥4.

7. The preparation method according to claim 4, characterized in that: The pre-reaction comprises: pre-reacting at 135-145° C. for 60-90 minutes under a protective gas atmosphere; After the pre-reaction is completed, the reaction system is heated to 280-320°C. At the end of the reaction, a vacuum degree of 1-5 mbar is provided to remove by-products in the reaction system. The negative pressure time is 10-90 minutes. The cooling is natural cooling under protective gas conditions; After said cooling, the ground product is pulverized.

8. The preparation method according to claim 7, characterized in that: The protective gas is nitrogen or an inert gas.

9. Use of the polyester imide polymer according to claim 1 in the fields of special engineering plastics and high-performance fibers.

Citation Information

Patent Citations

  • Liquid crystal polymer as well as preparation method and application thereof

    CN116178689A

  • Synthesis of thermatropic ciquid crystal polyester imide

    CN1121087A

  • Manufacturing method of liquid crystal polymer sheet

    JP2005153148A

  • Liquid crystal polyester composition, reflective plate and light-emitting device

    US20120026741A1

  • Crystalline polyester-imide, process for production thereof, and use thereof

    US4760124A